Оновлення американської медичної освіти на початку ХХ ст.: погляди А. Флекснера - Куліченко, Алла Костянтинівна; Куличенко, А. К.; Kulichenko, Alla (Суми: СумДПУ, 2018)
У статті розглянуто погляди американського педагога та критика А. Флекснера (1866–1959) щодо реформи медичної освіти США на початку ХХ ст. Зокрема, увагу зосереджено на праці «Медична освіта США та Канади. Доповідь для фонду Карнегі щодо поліпшення викладання» (1910), відомої як «Доповідь Флекснера». У розвідці автор виокремлює передумови реформи та ключові рекомендації А.Флекснера, що стосуються змін у системі американської медичної освіти, а саме: основні завдання, структурні підрозділи, професорсько-викладацький склад, матеріально-технічне забезпечення, методи навчання, організація навчального процесу у медичних школах тощо. В статье рассмотрены взгляды американского педагога и критика А. Флекснера (1866-1959) касательно реформы медицинского образования США в начале XX в. В частности, внимание сосредоточено на работе «Медицинское образование США и Канады. Доклад для фонда Карнеги по улучшению преподавания» (1910), известной как «Доклад Флекснера». В исследовании автор выделяет предпосылки реформы и ключевые рекомендации А. Флекснера, касающиеся изменений в системе американского медицинского образования, а именно: основные задачи, структурные подразделения, профессорско-преподавательский состав, материально-техническое обеспечение, методы обучения, организация учебного процесса в медицинских школах и т.д.Until becoming the world leader in medical education, the USA were carrying out various decisive and effective reforms during the 20th century. It is noted that philanthropic organizations and foundations played an important role in the reform of the medical educational paradigm. The outstanding representative of one of these organizations was A. Flexner (1866–1959) – an educator and a critic whose vision of improving medical education became successful and the key one, despite numerous discussions in the academic circles. A. Flexner introduced important recommendations concerning reforming the medical education in his work “Medical Education in the United States and Canada: A Report to the Carnegie Foundation for the Advancement of Teaching” (1910) also known as “Flexner Report”. The aim of the paper is to highlight the preconditions of the reform in medical education in the early 20th century, and to point out Flexner’s recommendations in the context of the medical educational paradigm. In this paper, the author deals with such methods as general scientific ones (analysis, synthesis, systematization, and generalization)  to provide the holistic view of the content of A. Flexner’s ideas concerning the medical education reform in the USA; search-bibliographic method  to study and systematize the scientific and pedagogical literature on the research subject; pedagogical reconstruction to reproduce historical and pedagogical reality in American medical education in the early 20th century. Thus, there were many factors that caused changes in medical education in the USA. Among them there were social, demographic, economic, political and biological (population health) ones. As for Flexner’s recommendations in the context of the medical educational paradigm, they are the main tasks, structural units, faculty, material and technical support, teaching methods, organization of the educational process in medical schools, etc. Besides, A. Flexner proposed to divide the existing medical schools into 3 main categories (A, B, C), and to focus on The Johns Hopkins University School of Medicine. As for the prospects of further research, we are going to describe the influence of Flexner’s recommendations on the development of the US medical education in the 20th century.
Обновление американського медицинского образования в начале ХХ ст.: взгляды А. Флекснера.
Upgrading American medical education in the early 20th century: A. Flexner’s views.
Keywords: американська медична освіта; передумови реформи; реформа; рекомендації; педагогічні погляди; А. Флекснер; Доповідь Флекснера; медична школа; студент; американское медицинское образование; предпосылки реформы; рекомендации; педагогические взгляды; А. Флекснер; Доклад Флекснера; медицинская школа; American medical education; preconditions of reform; reform; recommendations; pedagogical views; A. Flexner; Flexner Report; medical school; student